2007
DOI: 10.1016/j.molcel.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The Site of Action of Oxazolidinone Antibiotics in Living Bacteria and in Human Mitochondria

Abstract: The oxazolidinones are one of the newest classes of antibiotics. They inhibit bacterial growth by interfering with protein synthesis. The mechanism of oxazolidinone action and the precise location of the drug binding site in the ribosome are unknown. We used a panel of photoreactive derivatives to identify the site of action of oxazolidinones in the ribosomes of bacterial and human cells. The in vivo crosslinking data were used to model the position of the oxazolidinone molecule within its binding site in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
170
1
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(187 citation statements)
references
References 47 publications
(80 reference statements)
7
170
1
9
Order By: Relevance
“…In contrast, recent studies using an elegant in vivo cross-linking approach revealed the PTC as the bone fide drug target (12,13). These latter studies are consistent with the observation that drug resistance in both archaea and bacteria arises through mutation of nucleotides located within the PTC [ Fig.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…In contrast, recent studies using an elegant in vivo cross-linking approach revealed the PTC as the bone fide drug target (12,13). These latter studies are consistent with the observation that drug resistance in both archaea and bacteria arises through mutation of nucleotides located within the PTC [ Fig.…”
supporting
confidence: 75%
“…also to the ribosomal elongation factor LepA (12,13). LepA is a translational GTPase that binds to POST state ribosomes inducing a back-translocation to the PRE state (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While oxazolidinones are protein synthesis inhibitors that bind to the ribosome, it has taken a number of years to identify the binding site and most likely mode of action 28. In 2008, two reported X‐ray co‐crystal structures of linezolid bound to 50S ribosomal subunits confirmed the previously established site of action and suggested a mode of action (Figure 4).…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 94%
“…The first involves mutations in the 23S rRNA central loop of domain V, the peptidyl transferase center. While some of the mutated residues interact directly with the oxazolidinone, many do not but are instead used to stabilize the region surrounding the oxazolidinone 28. Mutations in these residues lead to small conformational changes of the linezolid binding pocket, which adversely affects drug binding.…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%